Public Disclosure and Consumer Financial Protection - Dou, Yiwei; Roh, Yongoh (Journal of Financial and Quantitative Analysis, 2024)
Abstract The U.S. Consumer Financial Protection Bureau has released a database of consumer complaints about banks’ financial products to the public since 2013. We find a greater reduction in mortgage applications to banks that receive more mortgage complaints in local markets after the disclosures. The effect is stronger in areas with more sophisticated consumers and higher credit competition, and for banks receiving more severe complaints. The number of monthly mortgage complaints per bank exhibits faster mean reversion after the publication of the database. These findings suggest that the public disclosure of mortgage complaints enhances product market discipline and consumer financial protection.